PARASITIZATION, PARASITISM, AND COMPARISON OF SEX RATIO OF Telenomus remus TO EGGS OF Spodoptera frugiperda ON CORN PLANTS IN KULON PROGO REGENCY - Chiquita Almira; Ichsan Luqmana Indra Putra (Agrovigor, 2026)
Spodoptera frugiperda is an invasive pest that causes severe damage to maize crops in Kulon Progo Regency. One biological control effort against this pest is the use of the egg parasitoid Telenomus remus. This study aimed to analyze the parasitization rate, parasitism rate, sex ratio, and their correlations in T. remus parasitizing S. frugiperda eggs in maize fields in Kulon Progo Regency. Egg samples were collected from maize fields using a W-pattern scouting method and reared under laboratory conditions until adult parasitoids or host larvae emerged. The number of parasitized eggs, successful parasitoid emergence, and the proportion of female and male individuals were recorded. The results showed that T. remus exhibited a relatively high parasitization rate, while the parasitism rate was moderate, with a female-biased sex ratio. Correlation analysis indicated that parasitization rate, parasitism rate, and sex ratio were not significantly correlated. These findings indicate that the developmental success of T. remus is influenced more by the biological condition of host eggs than by the number of eggs parasitized.